Implementasi Buku Besar Berbasis Web sebagai Penunjang Sistem Pelaporan Keuangan di PT. Sweelee Musika - Ruwatie, Yulia; Supranata, Mardani (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study aims to evaluate the implementation of a web-based general ledger system as a supporting tool in the preparation and submission of financial reports. The approach used in this research is a quantitative descriptive method that aims to provide an verview of the effectiveness of the implemented system. The development of the ccounting system was carried out by utilizing free templates available online, and then adjusted to the operational needs of Lebra Laundry MSMEs. The main objectives of implementing this web-based system are to minimize transaction recording errors, improve the efficiency of the financial recording process, and provide accurate and relevant financial information for management. The developed system allows recording transactions and preparation of financial reports automatically through a web-based platform that can be accessed anytime and anywhere. The results showed that the implementation of a web-based accounting system carried out by PT Sweelee is very effective. The advantages of this system lie in ease of access, increased accuracy in preparing financial reports, and the ability to present data in real time. Thus, this system provides added value for management in the process of making strategic decisions that are based on reliable and timely financial data.